PEOPLE, POWER AND PROFITS : PROGRESSIVE CAPITALISM FOR AN AGE OF DISCONTENT - Stiglitz, Joseph ([London] : Penguin Books, 2020)
In this book Stiglitz identifies the true sources of wealth and of increases in standards of living, based on learning, advances in science and technology, and the rule of law. He shows that the assault on the judiciary, universities, and the media undermines the very institutions that have long been the foundation of America's economic might and its democracy. Helpless though we may feel today, we are far from powerless. In fact, the economic solutions are often quite clear. We need to exploit the benefits of markets while taming their excesses, making sure that markets work for us-the U.S. citizens-and not the other way around. If enough citizens rally behind the agenda for change outlined in this book, it may not be too late to create a progressive capitalism that will recreate a shared prosperity. Stiglitz shows how a middle-class life can once again be attainable by all. An authoritative account of the predictable dangers of free market fundamentalism and the foundations of progressive capitalism, People, Power, and Profits shows us an America in crisis, but also lights a path through this challenging time.
Introduction -- Toward a more dismal economy -- Exploitation and market power -- America at war with itself over globalization -- Finance and the American crisis -- The challenge of new technologies -- Why government? -- Reconstructing American politics and economics : the way forward -- Restoring democracy -- Restoring a dynamic economy with jobs and opportunity for all -- A decent life for all -- Reclaiming America -- Acknowledgments -- Notes -- Index.
Includes bibliographical references and index.
Keywords: Wealth -- Social aspects -- United States; Rich people -- Social aspects -- United States; Corporations -- Social aspects -- United States; United States -- Economic policy -- 21st century